Pozycja Polski na międzynarodowym rynku badań rynkowych - Śmiłowski, Eugeniusz; Idzik, Marcin (Position of Poland on the International Market of Research Market, 2006)
The results of an analysis concerning the Polish market of research market with reference to the European and international markets are presented in this study. A lot of features common to the Polish and world markets are pointed out. Poland ranks 21-st in the global research market considering the level of income of the research business. There is a substantial differentiation in dynamics growth of the research market, especially among the new European Union member states. Domestic research markets are dominated by local clients, with a gradual increase in involvement of international clients in the structure of revenue. The business structure of the global research market is dominated by consumer surveys. The applied survey techniques indicate to Poland's delay with regard to the use of modem survey techniques.
Prace Naukowe Akademii Ekonomicznej we Wrocławiu; 2006; nr 1107, s. 131-142